COMPARATIVE EVALUATION OF DIFFERENT DOSES OF VINPOCETINE ALONE AND IN COMBINATION WITH SULFASALAZINE IN EXPERIMENTALLY INDUCED INFLAMMATORY BOWEL DISEASE IN RATS - Datt, Nishtha; Patyar, Rakesh Raman; Patyar, Sazal (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Inflammatory bowel disease (IBD) is a disorder characterized by chronic inflammation of the gastrointestinal tract and its exact etiopathology is still unclear. Most of the currently available drugs provide the symptomatic improvement, and their long-term use can lead to various unwanted effects also. This study was done to observe the effects of vinpocetine alone and in combination with sulfasalazine on IBD in rats. Methods: Adult Wistar rats of either sex were used (n=36). Experimental colitis was produced by intracolonic administration of acetic acid (10% v/v, 0.20 ml/rat) given per rectally. Rats were divided into six groups (n=6): Group I - normal control (0.9% w/v saline, intracolonic administration + 0.5% w/v carboxymethyl cellulose, i.e., CMC, p.o); Group II - acetic acid (10% v/v, intracolonic administration+0.5% w/v CMC, p.o); Group IIIA - acetic acid + vinpocetine (5 mg/kg, p.o); Group IIIB - acetic acid + vinpocetine (10 mg/kg, p.o); Group IV - acetic acid + sulfasalazine (360 mg/kg, p.o.); Group V - acetic acid + sulfasalazine + vinpocetine (360 mg/kg, p.o. + 5 mg/kg, p.o). The study period was of 15 days in which animals were treated with acetic acid solution on day 1 and treatment was started 4 hrs after the administration of acetic acid till the 14th day. On 15th day, the animals were sacrificed for the investigation of various macroscopic, microscopic, and biochemical parameters. Results: The higher dose of orally administered vinpocetine (10 mg/kg) and combination of sulfasalazine + vinpocetine (360 mg/kg + 5 mg/kg) were found to be the most effective in reducing the severity of mucosal damage which was similar to the reference drug sulfasalazine (360 mg/kg). Both the doses of vinpocetine curtailed the histopathological scores. The combination therapy of sulfasalazine + vinpocetine (360 mg/kg + 5 mg/kg) was equally effective to standard drug but not found to be the most effective treatment. Myeloperoxidase levels were significantly reduced in vinpocetine treated groups as compared to acetic acid control group, while the glutathione levels were increased significantly. Similarly, vinpocetine significantly decreased the malondialdehyde level in the intestinal tissue of the rats with acetic acid induced colitis, and thus the severity of the tissue damage. Conclusion: The results of this study indicated that vinpocetine possesses anti-inflammatory activity and are therapeutically effective in acetic acid induced ulcerative colitis at a dose of 5 mg/kg. More pronounced effects were observed at higher dose, i.e., 10 mg/kg. The combination of sulfasalzine + vinpocetine was also found to be effective as compared to high dose of vinpocetine (10 mg/kg).